Relevansi Teori Auguste Comte dalam Pengembangan Manajemen Pendidikan Modern - Alfiandrizal Alfiandrizal; Silfia Hanani; Indra Devi; Aisyah Syafitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In the context of modern education management, Auguste Comte's theory offers a valuable contribution in shaping thought and practice. The relevance of Comte's theory is not limited to one aspect of education management, but involves various dimensions such as scientific understanding, adaptation to social change, character and moral building, and the role of education in the evolution of society. The purpose of this study is to explain the Relevance of Auguste Comte's Theory in the Development of Modern Education Management. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. Sources of information in this study were reviewed from various novel sources of literature, research reports, scientific essays, theses, dissertations and posts both print and electronic related to the Relevance of Auguste Comte's Theory in the Development of Modern Education Management. The results of this study show that Comte's thought, especially the concept of positivism, the role of science in education, social evolution, morals, and the role of education in the development of society, has a significant impact on educational thinking and practice. The application of Comte's principles in education management allows us to design education that is based on evidence, science and scientific approaches. In addition, an understanding of social evolution helps us adapt to changes in society, while a focus on the formation of character, morals and social values supports the development of responsible individuals in society.